Benefits of e-cigarettes in smoking reduction and in pulmonary health among chronic smokers undergoing a lung cancer screening program at 6 months. (April 2020) - Lucchiari, Claudio; Masiero, Marianna; Mazzocco, Ketti; Veronesi, Giulia; Maisonneuve, Patrick; Jemos, Costantino; Omodeo Salè, Emanuela; Spina, Stefania; Bertolotti, Raffaella; Pravettoni, Gabriella
Highlights: E-cigarettes are common in smokers, but results on effectiveness are divergent. No significant differences observed in abstinence between groups. Nicotine e-cigarettes reduced cigarette consumption and cough smoking-related. Nicotine-free cigarettes have an impact in reducing smoking only at 3 months. No severe side effects related to e-cigarettes are reported at 3 and at 6 months. Abstract: Introduction: Electronic cigarettes (e-cigarettes) might be a valid and safe device to support smoking cessation. However, the available evidence is divergent. The aim of the present work was to assess the effects of an e-cigarette program on pulmonary health (cough, breath shortness, catarrh) and to evaluate the effectiveness of e-cigarettes in reducing tobacco consumption. Methods: The study is a double-blind randomized controlled trial. Two hundred and ten smokers were randomized into three groups: nicotine e-cigarette (8 mg/mL nicotine concentration), nicotine-free e-cigarettes (placebo), and control with 1:1:1 ratio. All participants received a 3 months cessation program that included a cognitive-behavioral intervention aimed at supporting people in changing their behavior and improving motivation to quit. Results: Pulmonary health, assessed with self-reported measures, clinical evaluations and the Leicester Cough Questionnaire, improved in participants who stopped smoking compared to their own baseline. No differences in pulmonary health were found between groups. Statistical tests showed a significant effect of Group (F (2, 118) = 4.005, p < .020) on daily cigarette consumption: after 6 months participants in the nicotine e-cigarette group smoked fewer cigarettes than any other group. Moreover, participants in this group showed the lowest level of exhaled carbon monoxide (CO) (M = 12.012, S.D. = 8.130), and the lowest level of dependence (M = 3.12, S.D. = 2.29) compared to the nicotine-free e-cigarette and control conditions. Conclusions: After 6 months about 20% of the entire sample stopped smoking. Participants who used e-cigarettes with nicotine smoked fewer tobacco cigarettes than any other group after 6 months (p < .020). Our data add to the efficacy and safety of e-cigarettes in helping smokers reducing tobacco consumption and improving pulmonary health status.